Effects Of Effort Praise On Selfefficacy, Growth Mindset And Englishspeaking Proficiency For A Student With Learning Difficulty In An Afterschool Language Enrichment Class - Wang, Hao (2024)
The students with learning difficulties in this study refers to those students with the behaviour of fidgeting, squirming, restless, sitting still trouble and rules breaking in class. This study aimed to investigate how the effort praise effect the self-efficacy, growth mindset, and speaking English proficiency of a student with learning difficulty. A mixed-method, single-case study design was used for data collection. Research questionnaires and scales were adopted for quantitative research, while interviews were utilized in the qualitative research. The study consisted of two phases. Phase 1 investigated self-efficacy, growth mindset and English ability of both the students without learning difficulties and with learning difficulty to explore the possible gaps. Phase 2 investigated the effect of using effort praise in an English after-school program on self-efficacy, growth mindset and English-speaking proficiency, utilizing both quantitative data and qualitative methods. In this study, one 10-year-old student with learning difficulty has already been selected for the study using purposive sampling and effort praise intervention has been set. The findings showed the levels of selfefficacy, growth mind and English ability of students without learning difficulties are higher than those of students with learning difficulties. The findings also showed effort appraise plays an important role to help student with learning difficulty improve their self-efficacy, growth mindset and English-speaking proficiency.